2009
DOI: 10.1073/pnas.0812367106
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic control of negative feedback regulators of NF-κB/RelA determines their pathogen- and cytokine-receptor signaling specificity

Abstract: Mammalian signaling networks contain an abundance of negative feedback regulators that may have overlapping (''fail-safe'') or specific functions. Within the NF-B signaling module, I B␣ is known as a negative feedback regulator, but the newly characterized inhibitor I B␦ is also inducibly expressed in response to inflammatory stimuli. To examine I B␦'s roles in inflammatory signaling, we mathematically modeled the 4-I B-containing NF-B signaling module and developed a computational phenotyping methodology of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 28 publications
5
119
0
Order By: Relevance
“…The complexity of the negative feedback on NF-B, involving mediators such as IB␦, as well as IB-␣, -␤, and -⑀, may include stimulus specific responses and different, but specified kinetic rate constants (25)(26)(27)(28). Also, the protein content of RelB was reported to be significantly reduced when p105 and p100 were absent, suggesting that the noncanonical pathway may be FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the negative feedback on NF-B, involving mediators such as IB␦, as well as IB-␣, -␤, and -⑀, may include stimulus specific responses and different, but specified kinetic rate constants (25)(26)(27)(28). Also, the protein content of RelB was reported to be significantly reduced when p105 and p100 were absent, suggesting that the noncanonical pathway may be FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…Because p100 expression is inducible by RelA:p50, this forms a negative feedback loop that has slow kinetics, yet is not degraded when canonical IKK activity persists. Computational simulations-directed experimental studies revealed that IκBδ forms a negative feedback loop to regulate RelA:p50 activity in a stimulus-specific manner, such that it is effective to LPS but not to TNF [3]. Indeed, the work revealed that IκBα provides effective negative feedback only to cytokine stimuli that produce transient canonical IKK activity.…”
Section: Kinetic Control Of the Canonical Pathwaymentioning
confidence: 99%
“…Moreover, size exclusion chromatography analyses suggest that IκBδ activity is mediated by a ~650 kDa high molecular weight npg complex, termed the IκBsome, which also contains IκBγ activity from p105 protein [2]. The pathways that govern IκBsome assembly and degradation are critical for regulating NFκB activity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because expression of all IκBs, barring IκBβ, is under feedback regulation by NF-κB, postinduction synthesis of these inhibitors dampens the nuclear activity of NF-κB by preventing it from undergoing persistent gene activation (3). This negative feedback loop is critical to involvement of IκBδ in long-lasting signals to pathogenic stimuli such as lipopolysaccharides; in contrast, other IκBs mediate signals for rapid NF-κB activation (19,20).…”
mentioning
confidence: 99%